The Effect of Voltage Quality Variations on The Performance and Operational Lifespan of Electronic Equipment in the Electrical System of Educational Buildings - Salsanabila Mariestiara Putri; Asro; Tb. Ade Rahmatullah; Mujiburohman; Amir Akbar Wicaksono (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the effect of voltage quality variations on the performance and estimated operational lifespan of electronic equipment. The study uses a quantitative explanatory approach with a field measurement design (in-situ) through the use of a power quality analyzer and supporting instruments. Data were analyzed using descriptive statistics, correlation analysis, and multiple linear regression. The results show that voltage quality variations occur unevenly, with the highest level of disturbances in areas with high electronic load density. Total harmonic distortion (THDv), voltage sag, and voltage unbalance are the most dominant factors influencing performance degradation and accelerating equipment operational degradation. The regression model shows a significant effect with strong explanatory power. This study confirms that voltage quality variations directly impact short-term performance and contribute to equipment operational lifespan reduction through the accumulation of electrical and thermal stress, making power quality management a crucial aspect in improving system reliability and efficiency of educational building facility management